2022
DOI: 10.3324/haematol.2021.280433
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of relapsed or refractory acute B-lymphoblastic leukemia patients and <i>BCR-ABL</i>-positive blast cell crisis of B-lymphoid lineage with extramedullary disease receiving inotuzumab ozogamicin

Abstract: Acute lymphoblastic leukemia (ALL) can relapse in the extramedullary compartment, with or without medullary involvement. Response to treatment may be unique. We evaluated response to inotuzumab ozogamicin (INO) in 31 relapsed/refractory (r/r) BALL patients with extramedullary disease (EMD). Median age was 31 (range, 19-81) years. All patients were heavily pretreated, including allogeneic hematopoietic stem cell transplantation (allo-HCT; n=18). Overall response rate after two INO cycles was 84% (complete remis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…49 In a retrospective analysis of 31 adults with r/r B-ALL or lymphoid blast crisis with non-CNS EMD, the CR rate was 55%, with 2-year OS of 18%. 53 Furthermore, 4 out 59 inotuzumab responders and 2 out of 41 SOC responders relapsed with EMD. 49 In contrast to blinatumomab, inotuzumab appears to have potential activity in ALL with EMD, without excessive risk of EMD relapse after response.…”
Section: Emd and Cns Involvementmentioning
confidence: 99%
See 3 more Smart Citations
“…49 In a retrospective analysis of 31 adults with r/r B-ALL or lymphoid blast crisis with non-CNS EMD, the CR rate was 55%, with 2-year OS of 18%. 53 Furthermore, 4 out 59 inotuzumab responders and 2 out of 41 SOC responders relapsed with EMD. 49 In contrast to blinatumomab, inotuzumab appears to have potential activity in ALL with EMD, without excessive risk of EMD relapse after response.…”
Section: Emd and Cns Involvementmentioning
confidence: 99%
“…In a post‐hoc analysis of the INO‐VATE study in patients with baseline non‐CNS EMD, CR/CRi was reported in five out of seven patients treated with inotuzumab and two out of five patients treated with standard of care (SOC) 49 . In a retrospective analysis of 31 adults with r/r B‐ALL or lymphoid blast crisis with non‐CNS EMD, the CR rate was 55%, with 2‐year OS of 18% 53 . Furthermore, 4 out 59 inotuzumab responders and 2 out of 41 SOC responders relapsed with EMD 49 .…”
Section: Practical Considerations For Novel Therapies In R/r B‐allmentioning
confidence: 99%
See 2 more Smart Citations
“…Subanalyses in the INOVATE trial showed that the benefits of IO were more evident if used as first salvage therapy, 10 especially for patients who achieved negative measurable residual disease (MRD) 11 . Other studies demonstrated the benefit of IO even in B‐ALL patients irrespective of disease burden and in patients with disease with extramedullary involvement or B‐cell lymphoblastic lymphoma 12–14 …”
Section: Introductionmentioning
confidence: 99%